2022
DOI: 10.1177/17455057221096240
|View full text |Cite
|
Sign up to set email alerts
|

Cervical screening uptake: A cross-sectional study of self-reported screening attitudes, behaviours and barriers to participation among South Asian immigrant women living in Australia

Abstract: Introduction: Cervical cancer remains a major cause of morbidity and mortality among women from low and lower middle-income countries, as well as underserved population subgroups in high-income countries. Migration from South Asia to Australia has increased over the last decade, and immigrant women from this region have been reported as a subgroup, with less than optimal cervical screening participation in Australia. This study examined cervical screening uptake and associated behavioural attitudes among South… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Economic difficulties were also experienced by immigrant women in a study in Oslo, which found that immigrant women directed their focus towards meeting their family's basic needs rather than their own health concerns [ 6 ]. The lack of health insurance significantly reduced the desire of immigrant women in the US and Australia to attend a screening site [ 21 , 22 ]. Moreover, Islam et al (2017) reported that immigration status and fear of being deported often acted as barriers preventing many women from undergoing screening in the US [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Economic difficulties were also experienced by immigrant women in a study in Oslo, which found that immigrant women directed their focus towards meeting their family's basic needs rather than their own health concerns [ 6 ]. The lack of health insurance significantly reduced the desire of immigrant women in the US and Australia to attend a screening site [ 21 , 22 ]. Moreover, Islam et al (2017) reported that immigration status and fear of being deported often acted as barriers preventing many women from undergoing screening in the US [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Immigrant Muslim women from different ethnic backgrounds in European countries and Australia also described feeling shy when discussing CCS. This was also the experience of some Indian women and black women who perceived this as a barrier to screening, particularly among the older generation who feel that their body is a private and sensitive area [ 9 , 20 , 21 ]. Moreover, most women in the US, Canada, London, Scotland, and Dubai stated that pain during the CCS procedure and fear of cancer were major factors contributing to low CCS rates, followed by discomfort during the procedure [ 3 , 6 , 14 , 18 , 20 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations